THE EFFECT OF A STRATEGY (1-3-5-7) ON THE READING COMPREHENSION OF READING MATERIAL AMONG FOURTHGRADE LITERARY STUDENTS - Abdullah Ghaith Nafal (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims. To know the effect of the strategy (1-3-5-7) on the reading comprehension of reading material among fourth-grade literary students. To verify this, the researcher relied. An experimental design within the experimental designs with partial control and a final test for the two research groups, one of them experimental and the other control. The researcher chose (Al-Jumhuriya for Boys) high school, located in Baghdad governorate, and randomly selected class (b) to represent the adult experimental group. The number of its students is (38) students, and Division (C) to represent the control group of (37) students. The researcher conducted a parity between the students of the two groups in the following variables: (chronological age calculated in months, the educational achievement of the parents, and the scores of the language ability test). The researcher formulated (70) behavioral goals for the topics that students will study during the experiment. He prepared daily plans to teach the two research groups, and presented the two lesson plans for the two groups to a group of specialists to know its validity for literary fourth-grade students. He prepared a final test for reading comprehension divided into four sections, and applied it to the two research groups after the end of the experiment, which lasted for eight weeks, which began on Sunday 10/21/2018 and ended on Thursday (12/20/2018), applying the experiment himself. The researcher used the following statistical methods: the T-test for two independent samples, the chi-square (Ca2), the Pearson correlation coefficient, the equation of difficulty and discrimination coefficient, and the equation of the effectiveness of alternatives. The incorrect results, and after analyzing the results statistically, the researcher concluded: The students of the experimental group that studied the reading material using the strategy (1-3-5-7) outperformed the control group students, which taught the same material in the usual way of comprehending the recitation. According to these results, the researcher recommended: 1. Adopting a strategy (1-3-5-7) in teaching reading for the fourth literary grade. 2. Training Arabic language teachers on the strategy (1-3-5-7) to enable them to know students’ thinking processes. The researcher suggests: 1. Conducting a similar study of literature and texts for fourth-grade literary students. 2. Conducting a similar study in developing the literary appreciation skills of fourth grade literary students.